If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 + x = x + 19 Reorder the terms: -26 + x = 19 + x Add '-1x' to each side of the equation. -26 + x + -1x = 19 + x + -1x Combine like terms: x + -1x = 0 -26 + 0 = 19 + x + -1x -26 = 19 + x + -1x Combine like terms: x + -1x = 0 -26 = 19 + 0 -26 = 19 Solving -26 = 19 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(2-2x)+3(1-2x)=4 | | -43+r=-48 | | 3xy+21x+2y-14=0 | | x^2+36x+5=0 | | 63+14e=91 | | x^5+x^3=3x^2-178 | | 33+15w=3w-w+4 | | 3y^2-4x^2-5=0 | | x^2+15=23 | | 48=14+2x^2 | | t^2-4t=28-7t | | 42-6x=3x+17 | | 8-9x=49-16x | | -101-10x=10x+19 | | 4x-4=12x-28 | | 1.5/2= | | 6x+5y=90 | | 14x-109=5x-10 | | 5/8+1/2= | | 12a+120+20a=50a-10-18a | | -2(-3s+6s)=30-1s | | 134x+7=1578 | | 2x/5=(x+4)/3 | | 230-3x=42x+20 | | 13-8x=42x+20 | | 5x+13=83-5x | | 8n+4n= | | (X+2)/8=30/12 | | (x)(X+3)=4s-b | | 3x+x^2=36 | | -3(1-2)=30(0.8) | | (3x+5y)-(2x-3y)= |